O ethos da privação de liberdade como formador de saberes e representações de três professoras - Lena, Angela (2008)
This research aimed at understanding and interpreting the context of liberty privation as a knowledge and representations former of three teachers who work in the inserted school at CASE/SM (Social-Educative Attendance Center of Santa Maria), one of the attendance unit of FASE/RS (Social-Educative Attendance Foundation of Rio Grande do Sul), with the purpose of contributing to the knowledge production for teachers formation. Methodologically, this study presents ways searched that help in the analyzed data collection. It presents an ethnographic character since the author also works in that school as a teacher besides being the researcher. To interpret this study results, it was used the Philosophical Hermeneutics. As well as, life histories of the teachers called Subjects-Collaborators were used. They were analyzed in double perspective: of investigation and also formation. The main mean to collect data was a semi-structured interview. In relation to the results, the knowledge that was produced from this ethos required from the teachers an interpretation that, while aesthetics experience, was able to produce ethic-affective knowledge by utilizing it as an essential pedagogical technology to induce adolescents to participate in the activities proposed in class. The representations in relation to FASE point to education as a watched right, that, from the disciplinary ruling imposed to the adolescents private from liberty, is a biopolitical technology, correlated to the objective of reducing personal and social risks present in these students lives besides protecting the population that is threatened by them. The CASE, with its rules, permanent vigilance, makes difficulty the practice of some pedagogical innovations that the three teachers try to develop there. Considering what was analyzed, the teachers who want to work at confining systems will need to understand that each one its students is able to learn, however, each one at their times and in different ways. It is why it is so important a teacher could work only with few students in a classroom. In order to that become effective as a social practice in education, the teachers will need to develop o sensitive glance to each one of their students. In relation to the representations the teachers have about their pedagogical work in the adolescents re-socialization, after the extinction of the socio-educative measure, what become prominent is presented as an instituted possibility since they can not say about a work that will happen out of the institution. Therefore, it possible to affirm that FASE is an institution that works on the subjective side of people and also as a former of teaching work.